Czytanie jako działanie, dzieło jako zdarzenie. Czy możliwa jest poetyka literatury interaktywnej? - Winiecka, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article describes new phenomena in the field of literature that have developed under the influence of digital technology. It points out to the conversion of the ontology of works and modification of the nature of perception that are associated with digital media. Literature created in digital technology becomes an audiovisual and multimedia experience. Its audience is given a new kind of experience based on participation. Participation is related to interactivity, which is one of the basic features of digital objects. They need action rather than contemplation to reveal. The authoress points out that, in new literary phenomena, digital medium becomes an important part of the work. It influences its structure, functions, manner of existence, and strategies for impact on the recipient. Every act of interactive reading is transformed into a performance – a oneoff and a unique event. Reading is transformed from contemplation into action engaging the reader’s physicality. Description of this modification of literary communication and the poetics of reception can be the key to understanding the essence of e-literature.